Change in and continuity of traditional village architecture: the Bali Aga village of Tenganan Pegringsingan, Bali, Indonesia - Dwita Hadi Rahmi (Built Heritage)
Abstract Traditional architecture is a cultural expression of a community that has developed from time to time with changes in and continuity of its cultural values. There are cultural values that remain stable and can still survive in contemporary culture, whereas others change following the socio-cultural development of the community. There needs to be a balance between the change in and continuity of cultural values to achieve the sustainability of traditional architecture. Balance can be achieved if the core of its heritage, which is the cultural values of the community, is maintained and if the heritage values of old cultural products can be appreciated in contemporary culture. Tenganan Pegringsingan Village, a traditional Bali Aga village, has developed into a cultural tourism village. Most of its residents are involved in tourism activities, having opened art shops in their houses and selling crafts in the open spaces of the village. Problems arise when changes in the architecture of the village and residents’ houses, regarding which there is fear that they will affect the sustainability of residents’ traditional cultural values, increase. This study aims to examine the changes in and continuity of traditional architecture in the Tenganan Pegringsingan Village settlement. It observed the village and spatial layout of houses, conducted in-depth interviews with homeowners and village leaders, and was supported by data from questionnaires. Qualitative analysis was carried out, supported by maps, photos, and architectural drawings. This study revealed that there are changes in four elements of village architecture due to tourism, including village spatial design, the function and design of awangan (open space), the function and layout of houses, and building façades. The intervention of the government and the involvement of the community in tourism activities for economic interests have triggered many changes. However, the continuity of these components still exists because the village community continues to strongly hold traditional rules. Tenganan Pegringsingan Village is under threat due to the decline of its architectural continuity, which will obscure and degrade the cultural values of its heritage. The balance between the change in and continuity of the elements of village spatial design and houses, which is strongly influenced by the dynamics of the community’s cultural life, is the novelty of this architectural research.